Sosialisasi Peduli Lingkungan: Dari Desa Tanam, Rawat, dan Lestarikan Bersama KKM 36 Desa Kertasana Pandeglang: Pengabdian - Eli Apud Saepudin; Resty Yuliana; Raissa Adelio; Cici Istitika Indriani; Ima Muslimah; Yusuf Wijaya; Ahmad Yani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The Environmental Care Socialization Activity: From the Village Plant, Care, and Preserve Together with KKM 36 Kertasana Village, Pandeglang aims to increase public awareness and participation in maintaining the sustainability of the village environment. Through this program, KKM 36 invites residents to actively plant trees, care for existing plants, and preserve natural resources so that the sustainability of the village ecosystem can be maintained. The implementation method of the activity includes socialization, direct education to the community, and joint tree planting practices. The results of the activity show an increase in public understanding of the importance of environmental preservation and the creation of a shared commitment to maintaining the cleanliness and sustainability of Kertasana Village. This program is expected to be the first step in the formation of a sustainable environmental care movement and can be an example for other villages in the Pandeglang area.